Maksimalisasi Penggunaan Metode Profile Matching dalam Menentukan Kandidat Terbaik - Zainal Abidin; Indra Gita Anugrah; Ryco Puji Setyono (Teknik Informatika Universitas Pamulang, 2019)
Determine the best candidate in a company is something that is natural. There are several methods to determine the best candidate. One of them using the